The multiplicity of 250-μm Herschel sources in the COSMOS field. Issue 1 (3rd May 2016) - Scudder, Jillian M.; Oliver, Seb; Hurley, Peter D.; Griffin, Matt; Sargent, Mark T.; Scott, Douglas; Wang, Lingyu; Wardlow, Julie L.
Abstract: We investigate the multiplicity of extragalactic sources detected by the Herschel Space Observatory in the COSMOS field. Using 3.6- and 24-μm catalogues, in conjunction with 250-μm data from Herschel, we seek to determine if a significant fraction of Herschel sources are composed of multiple components emitting at 250 μm. We use the xid+ code, using Bayesian inference methods to produce probability distributions of the possible contributions to the observed 250-μm flux for each potential component. The fraction of Herschel flux assigned to the brightest component is highest for sources with total 250-μm fluxes <45 mJy; however, the flux in the brightest component is still highest in the brightest Herschel sources. The faintest 250-μm sources (30–45 mJy) have the majority of their flux assigned to a single bright component; the second brightest component is typically significantly weaker, and contains the remainder of the 250-μm source flux. At the highest 250-μm fluxes (45–110 mJy), the brightest and second brightest components are assigned roughly equal fluxes, and together are insufficient to reach 100 per cent of the 250-μm source flux. This indicates that additional components are required, beyond the brightest two components, to reproduce the observed flux. 95 per cent of the sources in our sample have a second component that contains more than 10 per cent of the total source flux. Particularly for the brightest Herschel sources, assigning the total flux to a single source may overestimate the flux contributed by around 150 per cent.